(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
Fruit juice is a liquid extract obtained by pressing or squeezing the natural juices from fruits. This study aimed to compare the microbial load in freshly prepared fruit juice, commercially sold fruit juice, and spoiled fruit juice. Samples were purchased from a market in the Mgbakwu area of Awka North. A total of eight commercially sold packaged juices were obtained. Fresh pineapple and orange juices were prepared aseptically and then divided into two portions: one was allowed to spoil, while the other was taken to the laboratory fresh for microbial analysis. Sixty milliliters of each spoiled and freshly prepared juice were taken to Conig-Simonne Biomedicals for microbial analysis.​Nutrient agar and Eosin Methylene Blue (EMB) agar were used for the isolation of microorganisms, and microbial counts were determined using plate methods. Freshly prepared fruit juices showed no microbial growth, while spoiled fruit juices had a higher microbial load of 2.50×10⁴ CFU/mL. The microorganisms isolated included Klebsiella pneumoniae, Enterococcus faecalis, Lactobacillus spp., Shigella flexneri, Proteus mirabilis, Citrobacter freundii, and Salmonella enterica.​This study demonstrates that both commercial and homemade fruit juices are safe for human consumption, provided they are handled hygienically and consumed shortly after preparation, as they showed no microbial growth. However, homemade and commercially sold spoiled fruit juices exhibited signs of microbial contamination. These findings provide insights into microbial spoilage mechanisms and can inform strategies for improving fruit juice preservation.